1997
DOI: 10.1143/jjap.36.5575
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Properties in Heteroepitaxial Ba0.6Sr0.4TiO3 Thin Films on SrRuO3/SrTiO3 Substrates

Abstract: Heteroepitaxial Ba0.6Sr0.4TiO3 thin films with thicknesses from 26 nm to 97 nm were grown on SrRuO3 bottom electrode films on SrTiO3 single crystal substrates. Although the films have a paraelectric composition, ferroelectric hysteresis was observed in displacement versus electric field (D–E) loops. The ferroelectricity is considered to be developed as a result of bi-axial stress, caused by lattice mismatch between the dielectric films and the bottom electrodes. The maximum difference in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The lattice parameters of the ASLs were determined using reciprocal space mapping (BRUKER AXS, Dis-cover8). Abe et al [12][13][14] reported that the ferroelectricity of BTO/ STO solid solution films was enhanced by the anisotropic lattice distortion. Commercial high-frequency planar analysis software (SONNET EM) was used to design the interdigitalelectrode pattern and to calculate the dielectric permittivity from the complex admittance measured.…”
Section: Artificial Ferroelectricity In Perovskite Superlatticesmentioning
confidence: 99%
“…The lattice parameters of the ASLs were determined using reciprocal space mapping (BRUKER AXS, Dis-cover8). Abe et al [12][13][14] reported that the ferroelectricity of BTO/ STO solid solution films was enhanced by the anisotropic lattice distortion. Commercial high-frequency planar analysis software (SONNET EM) was used to design the interdigitalelectrode pattern and to calculate the dielectric permittivity from the complex admittance measured.…”
Section: Artificial Ferroelectricity In Perovskite Superlatticesmentioning
confidence: 99%
“…9,10) If an in-plane lattice of a ferroelectric film is larger than that of the bottom electrode material, the preference for negative polarity of polarization over positive is created by the lattice deformation. As a result, nonswitching regions are formed in the ferroelectric thin film at the interfacial region near the bottom electrode.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] In turn, these anomalous lattice expansions are associated with interesting changes in the physical properties including enhancement of the ferroelectric transition temperature [ 7,11,13 ] and voltage-shifted ferroelectric hysteresis loops where the voltage shift scales linearly with thickness. [ 8,13,14 ] Despite this range of interesting work, no clear explanation for the effects has been developed, but it is generally considered that defects could play some role in the manifestation of these effects.…”
mentioning
confidence: 99%